International Production Relocation and Exports of Services - Pain, Nigel (OECD Publishing, 2005)
This paper explores the relationship between the relocation of international production and exports of services from the United States using a number of different panel data estimators for six different categories of services. A conventional export demand relationship is augmented by three different measures of the extent of international production relocation by US-based parent companies in service and non-service industries. Our results reveal considerable heterogeneity in the relationship...